2016
DOI: 10.1002/dta.1972
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of hygrine and cuscohygrine in illicit cocaine production establishes their use as markers for chewing coca leaves in contrast with cocaine abuse

Abstract: Hygrine (HYG) and cuscohygrine (CUS) are natural alkaloids of coca leaves but are not found in illicit cocaine seizures. Therefore, they were proposed as markers for coca chewing in contrast to cocaine abuse in urine and hair testing. In order to examine at which step of the illegal cocaine production these compounds are lost, coca leaves were processed according to an authentic procedure by extraction with lime and kerosene, re-extraction with sulphuric acid, and precipitation of coca paste with ammonia. Non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Cuscohygrine and anahygrine are the two major biomolecules present in the W. somnifera. Cuscohygrine is primarily used as a biomarker to distinguish a practice of cocaine abuse from coca chewing [ 57 ] and has never been identified or recognized for its antiviral potential. Likewise, anahygrine is also not known for any major health benefits or for antiviral potential.…”
Section: Resultsmentioning
confidence: 99%
“…Cuscohygrine and anahygrine are the two major biomolecules present in the W. somnifera. Cuscohygrine is primarily used as a biomarker to distinguish a practice of cocaine abuse from coca chewing [ 57 ] and has never been identified or recognized for its antiviral potential. Likewise, anahygrine is also not known for any major health benefits or for antiviral potential.…”
Section: Resultsmentioning
confidence: 99%
“…Based on ADMET properties, cuminaldehyde has ability to penetrate BBB and cross GIT while it weak HERG inhibitor (Table 1). Cuscohygrine is a pyrrolidine alkaloid found in several plants such as C. myrrha and coca leaves (Rubio et al 2017). An in silico study showed that cuscohygrine found in Withania somnifera can act as nicotinic ACh receptor agonist and may mediate anti-AD effects of Withania somnifera based formulation in traditional ayurvedic medicines (Remya et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…HYG and CUS are pyrrolidine alkaloids ( Figure 1 ) present in the coca plant. Both compounds are lost in the first step of illegal cocaine production, so they can be considered markers of legal consumption [ 5 ]. Cinnamoylcocaine, a tropane-derived alkaloid with physicochemical characteristics similar to cocaine (logP, pKa, etc.)…”
Section: Introductionmentioning
confidence: 99%